2020
DOI: 10.1002/dmrr.3229
|View full text |Cite
|
Sign up to set email alerts
|

Hypocretin/orexin modulates body weight and the metabolism of glucose and insulin

Abstract: Summary The hypocretin/orexin (Hcrt/orexin) unit affects the functions of the nervous, cardiovascular, gastrointestinal, and reproductive systems. Hcrt/orexin ligands and receptors have been localized to different parts of the central and peripheral nervous systems, cerebrospinal fluid and blood, exocrine (pancreas, salivary, lacrimal) as well as endocrine (pancreatic islets, pituitary, adrenal) glands. Several factors including stress, glucagon‐like peptide‐1 agonists, glutamate, nicotine, glucose, and hypogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 111 publications
2
10
0
Order By: Relevance
“…When the effects of all other parameters were excluded by stepwise multiple regression analysis, HOMA-IR was shown to be the first independent predictor of orexin-A (Table -2). This confirms the role of orexin-A in IR and T2DM disease [5,24] and that HOMA-IR is a strong predictor of T2DM development [25].…”
Section: Discussionsupporting
confidence: 76%
“…When the effects of all other parameters were excluded by stepwise multiple regression analysis, HOMA-IR was shown to be the first independent predictor of orexin-A (Table -2). This confirms the role of orexin-A in IR and T2DM disease [5,24] and that HOMA-IR is a strong predictor of T2DM development [25].…”
Section: Discussionsupporting
confidence: 76%
“…However, as we have previously shown that obese phenotype was caused by increased food intake, we speculate that the silencing of the IKKβ expression prohibited hyperphagiainduced obesity in HD mice. The orexin and A13 TH neuronal populations are involved in metabolism regulation (Adeghate et al, 2020;Shi et al, 2013) and they are affected in HD (Gabery et al, 2010;Hult et al, 2011;Petersen et al, 2005;Soylu-Kucharz et al, 2015). As the inactivation of the IKKβ signaling did not affect the preservation of these cells, we can speculate that orexin and A13 TH neuropathology are not the central cell populations responsible for the development of HD bodyweight alterations.…”
Section: Discussionmentioning
confidence: 94%
“…When the serum level of leptin is high for a long period of time, the hypothalamic neurons do not really sense that information any more. The brain thinks that the person is still hungry, thereby eating more to reach the point of satiety leads to developing obesity [44,45]. This will make the obesity even more severe.…”
Section: Obesity and Hormones Regulating Food Intake And Satietymentioning
confidence: 99%